Physically Secured Optical OFDM-PON by Employing Chaotic Pseudorandom RF Subcarriers - Chongfu Zhang; Wei Zhang; Xiujun He; Chen Chen; Huijuan Zhang; Kun Qiu (IEEE Photonics Journal)
We propose a chaos-based physically-enhanced secure scheme for orthogonal frequency division multiplexing-based passive optical network (OFDM-PON). This scheme employs a pseudorandom number sequence generated by a chaotic logistic map to control the frequencies of RF subcarriers. Due to the characteristic of chaos, these chaotic frequencies of RF subcarriers are difficult to be decrypted by an eavesdropper, which could greatly enhance the security of OFDM-PON. An experiment with 10-Gb/s 16 QAM-OFDM data is successfully transmitted over 20-km fiber, and it has confirmed that the proposed security scheme can protect the system from an eavesdropper or attacker, while keep a good performance for legal optical network units.